Peran Mahasiswa Kampus Mengajar Angkatan 7 Dalam Meningkatkan Motivasi Belajar Siswa di SD Negeri 75 Kota Bengkulu - yonda Ahmeiza Putry; Ade Tiara Yulinda; Andi Azhar; Ratnawili Ratnawili; Surya Ade Saputera (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2024)
This research aims to explore the role of Class 7 Teaching Campus students in increasing student learning motivation at SD Negeri 75 Bengkulu City. The research method used is qualitative with a case study approach. Data was collected through observation, interviews and document analysis. The results of the research show that Class 7 Teaching Campus students have a significant role in increasing student learning motivation at SD Negeri 75 Bengkulu City. They bring new enthusiasm and energy to the teaching and learning process, introduce innovative and interactive learning methods, and provide additional motivation through character building and educational counseling. Apart from that, the personal approach taken by students in building relationships with students also contributes to increasing learning motivation.